ACTUALIZATION OF THE CATUR PURUSA ARTHA TEACHINGS IN CULTIVATING AN ANTI-CORRUPTION CULTURE - I Wayan Sunampan Putra (International Journal of Interreligious and Intercultural Studies, 2025)
Human needs and wants are basically very complex, so humans try to find ways to fulfill them. In its fulfillment, sometimes bad ways can be done, one of them is by means of corruption. Corruption is a crime that is extraordinary and the most depraved in human life. Because, not only harming a person, but also harming the state in the form of state wealth. To overcome this problem, various efforts have been made, such as anti-corruption education by instilling existing values. One of them is religious values, where religion is used to be able to be part of overcoming the problem of corruption. This paper tries to describe anti-corruption with a Hindu ethical approach using qualitative methods, data obtained through observation, literature study, and online data searches. The data that has been collected, then the data is analyzed and presented with a qualitative descriptive. This paper aims to describe the definition, forms and factors of corruption. Then also described anti-corruption education based on Hindu religious teachings. The view of discorruption in Hinduism is unraveled in Hindu ethics. The cause of corruption is due to sad understanding. The form of anti-corruption in Hindu ethics is contained in the teachings of Catur Purusa artha about life management to be able to achieve the goals of human life.